PREVALENCE OF PARTIAL EDENTULISM BASED ON KENNEDY’S CLASSIFICATION IN MAXILLARY ARCH - A RETROSPECTIVE STUDY - Saravanan, Keerthika; Duraisamy, Revathi; Kumar MP, Santhosh (International Journal of Psychosocial Rehabilitation, 2025)
Purpose of classification of partial edentulous arches provides communication between dental colleges,students,techians about the case, for planning effective treatment and to design the partial denture. Prevalence of partial edentulism based on kennedy’s classification was studied to an extent in various populations but fews studies are carried out in our population background. Aim of the study is to evaluate prevalence of partial edentulism based on Kennedy’s classification in maxillary arch. A retrospective study was conducted by reviewing 46,000 patient records of University hospital for a period of nine months from June 2019 to March 2020.About 145 Consecutive case records containing information on patient’s age, gender, partial edentulism based on kennedy’s classification with signed informed consent were sorted.. Age of the patients were categorized as 21-30 years, 31-40years, 41-50 years, 51-60 years and above 60 years for statistical convenience. Descriptive statistics and chi square association test was employed to find the association between Age, Gender and Kennedy’s classification with a level of significance set at p<0.05. Final data set consisted of 145 patients out of which 96 (66.2 %) were males and 49 (33.8%) were females. Most of the participants (29.6%) were in the age group above 60 years.Significant association between age groups and kennedy’s classes was observed ( p= 0.000). No significant association between gender and Kennedy’s classes was observed ( p= 0.198). It can be concluded that in maxillary arch Kennedy’s class 1 was found to be most prevalent in the age group between 51-60 years. Kennedy’s class 2 was found to be prevalent in the age group above 60 years. Kennedy’s class 3 was found to be most prevalent in the age group between 41-60 years. Kennedy’s class 4 was found to be most prevalent in the age group between 21- 30 years.Gender has no effect on prevalence of Kennedy’s classes. However, age has significant association